Literasi Keuangan Terhadap Perilaku Konsumtif Dengan Kontrol Diri Sebagai Variabel Moderasi (Studi Pada Gen Z Kota Malang) - Amaliatul Khasanah; Mardiana Mardiana (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Generation Z is consuming habits are changing due to the advancement of digital technology, and they are becoming more prone to consumptive behavior. The purpose of this study is to examine how financial literacy affects consumptive behavior among Generation Z in Malang City, using self-control as a moderating variable. The study employed a quantitative methodology, gathering primary data from 165 respondents chosen through purposive sampling via an online questionnaire. With the use of SmartPLS 3 software, structural equation modeling was used to analyze the data. The findings demonstrated that consumptive behavior was significantly impacted by self-control but not by financial literacy. In addition, self-control was not proven to moderate the relationship between financial literacy and consumptive behavior. This study concluded that psychological aspects, especially self-control, have a more dominant role than financial knowledge in shaping the consumption behavior of Generation Z. These results are consistent with the theories of planned behavior, hedonic consumption, and self-control, which have significant ramifications for the creation of financial education and self-control-enhancing initiatives that support the same consumer behavior.